The Validity and Reliability Study of Revised School Climate Teacher Survey’s Turkish Version - Ferat Yılmaz; Serkan Demir (International Journal of Assessment Tools in Education)
It is aimed to adapt Revised School Climate Teacher Survey (RSCTS) which is developed with a character education perspective to Turkish and assess its psychometrics properties in this study. This study is an instrument adaptation study. There are three different study groups in this study. First group consists of 56 English teachers studied with to determine the linguistic equivalence. Second group consists of 58 teachers studied with to determine the concurrent validity. Third group consisting 240 elementary and secondary teachers was studied with to reveal the construct validity, measurement reliability and to analyze the items. Data collection tools of this study are RSCTS aimed to adapt and Organizational Climate Scale (OCS) used to determine concurrent validity of RSCTS. Based on the results of this study, it can be concluded that Turkish and English versions of RSCTS are equivalent at a high level with regard to linguistic equivalence. Furthermore, some sub-scales of RSCTS have concurrent validity. Construct validity of Turkish version of RSCTS was confirmed by Confirmatory Factor Analysis. According to item analysis, items in RSCTS can discriminate the participants remarkably. Considering measurement reliability coefficients and characteristics of the study group, it is possible to state that RSCTS can be used as a valid and reliable instrument to measure teacher’s perceptions about school climate in all of the school stages in Turkey.